City farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The belief that cities are for industry and that the countryside is for farming is outdated. Urban farms are a life-saver for millions of urban dwellers worldwide. A recent study of urban farming in 100 cities in 30 countries concludes that one in...